2004
DOI: 10.1038/sj.bjc.6601608
|View full text |Cite
|
Sign up to set email alerts
|

Serum bile acids and risk factors for colorectal cancer

Abstract: The ratio of deoxycholic acid to chenodeoxycholic acid in the serum of 62 men was inversely related to body mass index and to saturated fat intake after adjustment for body mass index, smoking, and age conversely, this ratio was associated positively with the intake of fibre from grains. Bile acids (BA) are potential risk factors for colorectal cancer (CRC). A small prospective study suggests that a high ratio of deoxycholic acid (DC) to cholic acid (CA) in serum is associated with an increased incidence of CR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 16 publications
0
2
0
1
Order By: Relevance
“…This study also identified that the ratio of GUDCA to UDCA and GCDCA to CDCA was significantly associated with shortened 5-year OS and RFS, respectively, in patients aged ≥ 55 years old. Multiple epidemiological studies have indicated that specific bile acids present in feces and blood samples are positively related to increased CRC risk, and one recent study revealed a correlation between bile acids and CRC outcomes [36][37][38][39][40], however these observations have not been consistently observed [38]. A recent prospective study showed that the prediagnostic abundance of GCDCA, in the serum is positively associated with risk of colon cancer [37].…”
Section: Discussionmentioning
confidence: 99%
“…This study also identified that the ratio of GUDCA to UDCA and GCDCA to CDCA was significantly associated with shortened 5-year OS and RFS, respectively, in patients aged ≥ 55 years old. Multiple epidemiological studies have indicated that specific bile acids present in feces and blood samples are positively related to increased CRC risk, and one recent study revealed a correlation between bile acids and CRC outcomes [36][37][38][39][40], however these observations have not been consistently observed [38]. A recent prospective study showed that the prediagnostic abundance of GCDCA, in the serum is positively associated with risk of colon cancer [37].…”
Section: Discussionmentioning
confidence: 99%
“…CRC development may take years and involve multiple risk factors [3,[69][70][71]. Intermediate steps have been observed.…”
Section: Clinical Implications: Colorectal Cancer Carcinogenesis Metastasis and Treatmentmentioning
confidence: 99%
“…No intuito de diminuir a incidência de cânceres do intestino grosso diversos estudos sugerem a ingestão de fibras como procedimento preventivo. Sabe-se que pigmentos biliares sob ação de microorganismos intestinais podem formar agentes carcinogênicos e co-carcinogênicos a partir da desidrogenação do núcleo dos ácidos biliares, sendo capazes de determinar em longo prazo o aparecimento de cânceres de cólon em indivíduos com trânsito intestinal lento ( van-Faassen et al, 2004). Por acelerarem o trânsito fecal, agem reduzindo a formação e conseqüente contato desses agentes cancerígenos com a mucosa intestinal (Lederer, 1990;Walker, 1993;Haber et al, 1977;Alabaster et al, 1997).…”
Section: Ide Efeitos Fisiológicos Das Fibras Alimentaresunclassified